Studi Perancangan Ruang Henti Khusus (RHK) Sepeda Motor Di Simpang Bersinyal (Studi Kasus Simpang Tugu Pecel, Simpang Ruang Terbuka Hijau (RTH) Kartini Dan Simpang Diponegoro Di Kota Madiun) - Wahana Lestari, Titik Nur; Amudi, Abdiyah; Anggraeni, Ayu Roesdyning Tyas Dyah (Department of Civil Engineering, Dr. Soetomo University, 2019)
The growth of motorcycle in Indonesia increased rapidly and is the most common vehicle on the highway, especially at a crossroads in the city of Madiun. As a result, there is often an accumulation of irregular motorcycle and breaking traffic at the junction in the red phase. This is indicated by motorcycle reaching more than 30 motorcycle at the junction in the red phase. That inflic the a conflicts that affect the movement of other vehicle. Related with this problem, to reduce the occurrence of conflict, needed traffic engineering by providing facility Advance Stop Lines (ASLs) at the Signed Intersection which is intended so that vehicle can exit from Intersection regularly and reduce the accidents at the Signed Intersection. The purpose of this research is knowing the Level Of Service (LOS) and determine the desain of Advance Stop Lines (ASLs) at Signed Intersection with research area is the Tugu Pecel Intersection, Ruang Terbuka Hijau Intersetion and Diponegoro Intersection in Madiun City. The method used in this research is the Indonesian Road Capacity Manual (MKJI,1997). The Level of Service (LOS) in existing condition is at Tugu Pecel Intersection is A (very good), at the RTH Kartini Intersection is E (bad) and Diponegoro Intersection is F (very bad). Design of Advance Stop Lines at the north approaching Tugu Pecel Intersection is 2 lanes with approach lanes (10,00 m × 1,00 m) and with an area of 6,75 m × 4,66 m, at the east approach of RTH Kartini Intersection is 2 lane with approach lanes (7,00 m × 1,00 m) and the area of 5,25 m ×4,66 m and the north Diponegoro Intersection are 2 aprroaching lanes with aprroac lanes (10,00 m ×1,00 m) and area 4,50 m ×4,66 m, south approach 2 lanes with approach lanes (7,00 m ×1,00 m) and area 4,50 m ×4,66 m, east approach is 2 lanes with approach lanes (9,50 m × 1,00m) and an area of 5,50 m ×4,66 m, the western approach is 2 lanes with approach lanes (7,00 m ×1,00 m) and an area 5,50 m ×4,66 m.